2016
DOI: 10.1002/ctpp.201500134
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of Inertial Confinement Fusion Plasmas

Abstract: In this paper the transport properties of non-isothermal dense deuterium-tritium plasmas were studied. Based on the effective interaction potentials between particles, the Coulomb logarithm for a two-temperature nonisothermal dense plasma was obtained. These potentials take into consideration long-range multi-particle screening effects and short-range quantum-mechanical effects in two-temperature plasmas. Transport processes in such plasmas were studied using the Coulomb logarithm. The obtained results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In previous works, within binary scattering approximation, various transport properties of dense plasmas with weakly degenerate electrons have been investigated using effective (screened) potential approach. [ 13–20 ] These investigations were limited to the equilibrium state. However, recently it was shown that the presence of the flux of electrons relative to ions leads to the creation of the wake field, which creates effective ion‐ion attraction regions.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, within binary scattering approximation, various transport properties of dense plasmas with weakly degenerate electrons have been investigated using effective (screened) potential approach. [ 13–20 ] These investigations were limited to the equilibrium state. However, recently it was shown that the presence of the flux of electrons relative to ions leads to the creation of the wake field, which creates effective ion‐ion attraction regions.…”
Section: Introductionmentioning
confidence: 99%
“…At present, theoretical and experimental study of plasma properties and plasma technologies is relevant due to significance for such practical applications as thermonuclear fusion [12][13][14][15], plasma medicine [16][17][18], the application of plasma technologies for surface treatment of materials [8][9][10], etc. In particular, the study of the optical properties of plasmas is important as gas discharge is now widely used in lighting devices of various types [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature relaxation between electrons and ions in dense plasma is a key problem in understanding the interactions in high energy density physics . Particularly for inertial confinement fusion (ICF), the values of energy transfer rates are necessary to simulate energy depositions . The experiments for diagnosing the process of temperature relaxation are currently advancing rapidly due to powerful lasers such as the OMEGA, X‐ray free electron lasers, and the National Ignition Facility .…”
Section: Introductionmentioning
confidence: 99%